(untitled) (Pulse, 2014)
Bypass grafts to the dorsalis pedis artery provide excellent revascularization to ischemic foot. It is a durable and effective procedure for limb salvage. Axillo femoral-popliteal procedure offers a reasonable alternative in high-risk patients. We are reporting 2 cases of such procedures from Apollo hospitals, Dhaka. Right Popletial to Dorsalis pedis artery anastomosis was done in a 32 years old man. Interposition venous graft was done from the right popliteal artery to dorsalis pedis artery. Axillo-Bi Femoral-Bi Poplileal Bypass Grafting: was done in a 59 years old man. Knitted fabric strength graft was used. Both the patients were doing well in postoperative period. DOI: http://dx.doi.org/10.3329/pulse.v5i2.20270 Pulse Vol.5 July 2011 p.65-71